Synthesis and Pharmacological Evaluation of Novel 4-Alkyl-5-thien-2'-yl Pyrazole Carboxamides - Lazzari, Paolo; Pau, Amedeo; Tambaro, Simone; Asproni, Battistina; Ruiu, Stefania; Pinna, Giansalvo; Mastinu, Andrea; M. Curzu, Maria; Reali, Roberta; Emilio Heiner Bottazzi, Mirko; A. Pinna, Gerard; Murineddu, Gabriele (Central Nervous System Agents in Medicinal Chemistry, 2012)
The synthesis of three series of novel 4-alkyl-5-(5'-chlorothiophen-2'-yl)-pyrazole-3-carbamoyl analogues of rimonabant with affinity for the CB1 cannabinoid receptor subtype is reported. Amongst the novel derivatives, compounds 21j, 22a, 22c, and 22f showed affinity values expressed as Ki ranging from 5.5 to 9.0 nM. Derivative 23e revealed a good CB1 affinity (Ki = 11.7 nM) and the highest CB1 selectivity of the whole series (KiCB2/KiCB1 = 384.6). These new compounds appeared to be able to pass the blood brain barrier and to counteract the activity of cannabinoid agonist. According to the results of mice vas deferens assays, as in the case of rimonabant, derivatives 21a, 22a, and 22b showed inverse agonist activity. In contrast, as a preliminary result to be confirmed, compound 23a exhibited neutral antagonist profile. According to the data obtained through an acute animal model, selected compounds 21a, 22a, and 23a evidenced the capability to significantly reduce food intake. At specific conditions, the effect of the novel compounds were higher than that induced by rimonabant. Amongst the novel CB1 antagonist compounds, 23a may represent a useful candidate agent for the treatment of obesity and its metabolic complications, with reduced side effects relative to those instead observed with rimonabant.
Keywords: Cannabinoid